Suprafenacine, an indazole-hydrazide agent, targets cancer cells through microtubule destabilization - Choi, Bo-Hwa (2014)
Microtubules are a highly validated target in cancer therapy. However, the clinical development of tubulin binding agents (TBA) has been hampered by toxicity and chemoresistance issues and has necessitated the search for new TBAs. Here, we report the identification of a novel cell permeable, tubulin-destabilizing molecule - 4,5,6,7-tetrahydro-1H-indazole-3-carboxy​licacid [1p-tolyl-meth-(E)-ylidene]-hydrazide (termed as Suprafenacine, SRF). SRF, identified by in silico screening of annotated chemical libraries, was shown to bind microtubules at the colchicine-binding site and inhibit polymerization. This led to G2/M cell cycle arrest and cell death via a mitochondria-mediated apoptotic pathway. Cell death was preceded by loss of mitochondrial membrane potential, JNK - mediated phosphorylation of Bcl-2 and Bad, and activation of caspase-3. Intriguingly, SRF was found to selectively inhibit cancer cell proliferation and was effective against drug-resistant cancer cells by virtue of its ability to bypass the multidrug resistance transporter P-glycoprotein. Taken together, our results suggest that SRF has potential as a chemotherapeutic agent for cancer treatment and provides an alternate scaffold for the development of improved anti-cancer agents.